Incarcerated students' experiences of UNISA’s open distance e-learning at one Medium Correctional Centre - Mdakane, M.; Ngubane, S. A.; Dhlamini, Z. S. (South African Journal of Higher Education, 2021)
Technology mediated pedagogies of the 21st century present new and unprecedented challenges for incarcerated tertiary students. The researchers, employing a qualitative exploratory research design, sought to explore the learning experiences of UNISA students incarcerated at Baviaanspoort Medium Correctional Centre. Six participants were sampled purposively and recruited to participate during a focus group interview. Qualitative content analysis revealed the ever-changing landscape of higher education due to the advent of digitised e-learning; the unique challenges encountered by incarcerated students studying at tertiary level; strategies for overcoming barriers associated with ODeL; and that lastly, in the context of imprisonment, student-centeredness is still primarily informed by a constructivist approach to ODL. The study concluded that students’ learning experiences, and by extension, academic success, can be enhanced provided learner support is augmented for incarcerated tertiary students.